Crosslinked Fibroin Nanoparticles: Investigations on Biostability, Cytotoxicity, and Cellular Internalization - Duy Toan Pham; Nuttawut Saelim; Raphaël Cornu; Arnaud Béduneau; Waree Tiyaboonchai (MDPI AG, 2020)
Recently, crosslinked fibroin nanoparticles (FNP) using the crosslinker 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) or the polymer poly(ethylenimine) (PEI) have been developed and showed potentials as novel drug delivery systems. Thus, this study further investigated the biological properties of these crosslinked FNP by labeling them with fluorescein isothiocyanate (FITC) for in vitro studies. All formulations possessed a mean particle size of approximately 300 nm and a tunable zeta potential (−20 to + 30 mV) dependent on the amount/type of crosslinkers. The FITC-bound FNP showed no significant difference in physical properties compared to the blank FNP. They possessed a binding efficacy of 3.3% w/w, and no FITC was released in sink condition up to 8 h. All formulations were colloidal stable in the sheep whole blood. The degradation rate of these FNP in blood could be controlled depending on their crosslink degree. Moreover, no potential toxicity in erythrocytes, Caco-2, HepG2, and 9L cells was noted for all formulations at particle concentrations of < 1 mg/mL. Finally, all FNP were internalized into the Caco-2 cells after 3 h incubation. The uptake rate of the positively charged particles was significantly higher than the negatively charged ones. In summary, the crosslinked FNP were safe and showed high potentials as versatile systems for biomedical applications.